2002
DOI: 10.1016/s1526-9523(01)00214-8
|View full text |Cite
|
Sign up to set email alerts
|

Late Entry Into Prenatal Care in a Rural Setting

Abstract: Social support, behavioral risk, and structural or demographic variables as well as acceptance of pregnancy were tested as determinants of late entry into prenatal care in a sample of 176 women in a rural county in California. The respondents were all those over age 18 served by four obstetric practices during a 4-month period ending in February 2000. One nurse-midwifery practice was included. Late entry into prenatal care during the first trimester occurred in 27.3% of the cases overall. Statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
12
1
1
Order By: Relevance
“…14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam. 26 Differences in culture or socioeconomic status or health knowledge including awareness on the importance of early booking for ANC or education level among study populations, or differences in time of study or study area whether urban or rural may also be responsible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 The timing of prenatal care initiation can be influenced by numerous prepregnancy factors, including maternal educational attainment, [1][2][3][4][5][6] age, [1][2][3][4][5][6][7][8] parity, 2,6,7 ethnicity, 3 women's feeling about pregnancy and prenatal care, 6 and insurance. 2,[8][9][10][11] In the last two decades, some investigators have demonstrated the importance of preconceptional care to improve perinatal outcomes. For example, it has been demonstrated that addressing periconceptional folic acid use at a preconceptional consultation improves folate use among women planning to conceive.…”
Section: Introductionmentioning
confidence: 99%